Colonies, general, original correspondence : CO 323 (Records of the National Archives., 2015)
Description: This series contains general records relating to the colonies. It includes: the records formerly known as 'Plantations General' among the Board of Trade correspondence, 1689 to 1780; Law Officers reports on colonial acts; applications for passports and colonial appointments; private correspondence of Earl Bathurst, 1822 to 1825, and R W Hay, 1825 to 1835; and correspondence, including circular despatches, relating to the colonies generally. Between 1801 and 1854, when the departments of War and the Colonies were under the same Secretary of State, much of the correspondence concerns both departments--copied from National Archives online catalogue entry (viewed April 14, 2015)